Semantic browsers or making browsers semantic - Senso, José-Antonio (Anuario ThinkEPI, 2008)
A semantic browser is any tool for browsing semantic content, or for browsing content based on semantic data. Other systems exist that let users make use of Semantic Web content within Web content as they browse the Web. The great unknown at present is how the market will decide which path to choose in developing browsers for the Semantic Web.